IMPROVING THE EFFICIENCY OF HOUSING AND COMMUNAL ECONOMY BY PREVENTING THE DEVELOPMENT OF CRISIS PROCESSES: Array - Dymchenko, O.; Rudachenko, O.; Kostylova, E.; Martemyanova, T.; Shkurupiy, K. (Municipal economy of cities. Series: «Economy science», 2019)
Crisis processes are an integral part of any system. They occur at different intervals in different spheres of human activity and at this point a broad classification of crises is formed, characterized by various factors. The nature of crises remains one of the most controversial and poorly understood problems. The greatest losses are caused by crises that occur unexpectedly, and theorists, upon their completion, prove their inevitability. Nowadays it is very important to have up-to-date information on crisis processes in the economy. It must be understood that one can extract usefulness from the current situation and what decisions should be taken to respond correctly and in time to the changes that are taking place in politics, economy and society. The peculiarity of crisis management of an enterprise is the increased complexity of administrative processes. The financial crisis is manifested in a lack of funds, an increase in arrears, a fall in sales, staff dissatisfaction and other adverse factors. Housing and communal services provide the process of life of the population of Ukraine. The urgency of the work is due to the fact that the traditional approach to determining the main aspects of the definition of debt is not exhaustive. The purpose of this work is to substantiate theoretical provisions for the management of accounts receivable, which will help to prevent crisis processes at utilities. The efficiency of the housing and communal services system is largely determined by the financial condition of the utilities, which function to ensure that the population of Ukraine is comfortable and provided with all life processes. The way to solve this problem is to conduct regular analysis and evaluation of the financial status of utilities. Diagnosis of prevention of crisis processes on the example of municipal enterprise "Kharkivvodokanal" is carried out. The receivables of the enterprise for consumed water supply services are projected on the example of Kharkivvodokanal utility using adaptive models. The results of the forecast indicate the inevitable crisis processes caused by rising debt. It is proved that the enterprise management needs to immediately implement anti-crisis measures aimed at finding a way out of the crisis.